2011
DOI: 10.3168/jds.2011-4676
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage potentials and antimicrobial resistance of Pseudomonas spp. isolated from cheeses

Abstract: Pseudomonas spp. are aerobic, gram-negative bacteria that are recognized as major food spoilage microorganisms. A total of 32 (22.9%) Pseudomonas spp. from 140 homemade white cheese samples collected from the open-air public bazaar were isolated and characterized. The aim of the present study was to investigate the biochemical characteristics, the production of extracellular enzymes, slime and β-lactamase, and antimicrobial susceptibility of Pseudomonas spp. isolated from cheeses. The identified isolates inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 22 publications
3
53
0
Order By: Relevance
“…isolated from bulk tank milk samples were the dominant non-coliform Gram-negative bacteria and showed the highest levels of resistance to antibiotics. In a recent study, Arslan et al (2011) verified that all 32 Pseudomonas strains isolated from cheese were susceptible to ciprofloxacin, gentamicin and imipenem. Antibiotic-resistant Pseudomonas spp.…”
Section: Susceptibility Of the Inhibitory Substances To Naohmentioning
confidence: 99%
See 1 more Smart Citation
“…isolated from bulk tank milk samples were the dominant non-coliform Gram-negative bacteria and showed the highest levels of resistance to antibiotics. In a recent study, Arslan et al (2011) verified that all 32 Pseudomonas strains isolated from cheese were susceptible to ciprofloxacin, gentamicin and imipenem. Antibiotic-resistant Pseudomonas spp.…”
Section: Susceptibility Of the Inhibitory Substances To Naohmentioning
confidence: 99%
“…Some differences in the diameters of the inhibition zones were observed in this experiment, but all the staphylococcal strains were inhibited by these Pseudomonas strains. Strain 8.2 was not included in these tests, since its spectrum of action and the plasmidial DNA profile (data not shown) suggested that this strain was identical to strain 8.1. literature, resistance to antibiotics has become common amongst strains isolated from milk and dairy products (ARSLAN et al, 2011;BEENA et al, 2011). Straley et al (2006) verified that Pseudomonas spp.…”
Section: Susceptibility Of the Inhibitory Substances To Naohmentioning
confidence: 99%
“…The result of the potentials of individual and a mixed bacteria culture to cause spoilage of 'native' soup is presented in Table 2. The average spoilage time for all seeded soups ranged from 15.15 to 16.00 h compared to the control samples' average spoilage time of 18.15 h. There is a dearth of information on the spoilage microorganisms of Nigeria soups, however, a number of Authors have reported P. aeruginosa, Alcaligenes faecalis and Proteus vulgaris as major food spoilage bacteria of 'ugba' (African oil bean seeds), meat and dairy [27,28,29,30,31,32,33].…”
Section: Isolated Bacteriamentioning
confidence: 99%
“…Genotypic analysis was not included because the objective of the study was to aim at eliminating any potentially pathogenic or food spoilage causing bacteria that may be present on food garnishes rather than target and eliminate specific bacteria. All the isolated organisms are known to cause food poisoning and/or food spoilage (Adams, 2000;Arslan, 2011, Doran, 1999Drake, 2007;Frost, 1995;Lund, 1993;Sabota, 1998;Silbernagel, 2001;Wogu, 2014).…”
Section: Eight Different Potentially Pathogenic And/or Spoilage Causimentioning
confidence: 99%